Carotid endarterectomy in acute ischemic stroke - A. N. Kazantsev; N. N. Burkov; R. S. Tarasov; A. I. Anufriev; A. R. Shabaev; E. V. Ruban; A. V. Mironov; V. Yu. Heraskov (Патология кровообращения и кардиохирургия, 2018)
Currently, there are no clear domestic and foreign recommendations for cerebral revascularization, also missing is a definite decision on determining the timing and possibility of carotid endarterectomy in acute ischemic stroke. A set of measures aiming at obtaining a satisfactory outcome of carotid endarterectomy in the acute ischemic cerebrovascular event is developed. To prevent hyperperfusion complications, a temporary shunt, low doses of unfractionated heparin, adequate antiplatelet, hypotensive and lipid-lowering therapy are used. The main advantages and disadvantages of all modern methods of surgical treatment of this condition are presented. Received 22 August 2017. Revised 7 December 2017. Accepted 11 December 2017. Funding: The study was supported by the Siberian Branch of Russian Academy of Sciences within the framework of the fundamental research package program. Conflict of interest: Authors declare no conflict of interest. Author contributions Drafting the article: A.N. Kazantsev Resources: A.R. Shabayev Artistic design: N.N. Burkov Critical revision of the article: A.I. Anufriyev, A.V. Mironov, V.Yu. Kheraskov Surgical treatment: A.N. Kazantsev Assistance in surgery: N.N. Burkov, A.R. Shabayev Revascularization tactic selection: A.I. Anufriyev, A.V. Mironov, V.Yu. Kheraskov Neurological examination: E.V. Ruban Final approval of the version to be published: A.N. Kazantsev, N.N. Burkov, R.S. Tarasov, A.I. Anufriyev, A.R. Shabayev, E.V. Ruban, A.V. Mironov, V.Yu. Kheraskov